Distribution and etiology of corm rot of gladiolus in Jammu Province of Jammu and Kashmir - VISHAL GUPTA; S.K. SINGH, VIJAY K. RAZDAN*, MOHD. TAHIR DAR, (Indian Phytopathology, 2014)
Soil borne diseases are the major constraints in the successful cultivation of gladiolus and a number of pathogens have been found to be associated such as Fusarium oxysporum f. sp. gladioli and Botrytis gladiolorum. In order to record the current status of soil borne diseases in gladiolus, periodical surveys were undertaken during 2010 and 2011. The disease was found to prevail in all the districts surveyed. The prevalence of disease was higher in 2010-11 as compared to 2009-10. Mycoflora found associated with the infected corms of gladiolus were Fusarium oxysporum f. sp. gladioli, Botrytis gladiolorum, Stromatinia gladioli and Penicillium sp. F. oxysporum f. sp. gladioli was the most dominant with an average occurrence of 82, 78 and 70%, whereas, B. gladiolorum had an occurrence of 42, 38 and 56% in Jammu, Kathua and Udhampur districts, respectively. Stromatinia gladioli occurred with the frequency of 10, 8 and 10 per cent and Penicillium sp. with the frequency of 4, 10 and 8 per cent in Jammu, Kathua and Udhampur districts, respectively. The weight loss was maximum (23.19%) in corms inoculated with combined inoculation of F. oxysporum f. sp. gladioli and B. gladiolorum, followed by inoculation of F. oxysporum f. sp. gladioli and B. gladiolorum individually.